Epidemiology in a changing world: implications for population-based research on mental disorders. (June 2014) - Cooper, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction and objectives. Population-based research on mental disorders needs to keep pace with trends in general epidemiology. At present, this requirement is complicated by uncertainty within the parent discipline about its future development. The present study examines proposals for new directions in strategy and methods and considers their significance for psychiatric epidemiology. Method. Narrative review, cross-checked by search of English-language journals of epidemiology for new trends and developments reported in the years from 2000 onwards. Results. The proposals reviewed here are divided into three groups: 1. A new research paradigm of 'eco-epidemiology', which includes both individual risk factors and macro-environmental systems that mediate population levels of health and sickness. 2. Improved 'translation' of research findings – i.e. more rapid and effective implementation of epidemiological evidence into health policy and practice. 3. Adaptation of epidemiology to a globalised economy, with firmer regulation of funding and resources. Conclusions. Each of these proposals has implications for psychiatric epidemiology. Workers in this field, however, are still preoccupied by relatively specific problems of definition, measurement and classification, and so far the current debates in general epidemiology are scarcely reflected. The proposals outlined above call for: a working model of eco-epidemiology as it relates to psychiatric disorders; implementation strategies to encourage more active participation in epidemiological research by community health services and caregiver organisations; international collaborative projects that offer practical benefits in training and service facilities for the countries taking part.